Engineering Education-Present Scenario and Need for Research - Junnarkar, N. D.; Reosekar, Ravi (Journal of Engineering Education Transformations, 2011)
This study concentrates on engineering education in the sub continental part of the fast developing Asian country, India. The study helps in finding out the perception of education stakeholders about the quality in engineering education. It is proposed to validate or otherwise, the following hypotheses. The hypotheses are 1. Student feed back about the education process contributes significantly towards enhancing the quality of education 2. A clear mission, objective and commitment of the management towards satisfaction of the stakeholders in the institute is necessary to improve the quality of education in the institute 3. Research Development and Training activities through faculty development programs goes a long way towards enhancing quality of education. Real time data has been collected from different engineering colleges of one of the states of the fast developing country, India. The data is from 10 colleges with different background based on location, age and students’ gender. Results indicate the factors responsible for governing the quality of education and the perception of stakeholders about the same.